Additional Results From SECURE - Shuman, Jill (MD Conference Express, 2015)
Data from the SECURE trial suggested that isavuconazole was not inferior to voriconazole when treating invasive fungal diseases. Data from 2 subsets of SECURE now show that patients taking isavuconazole are less likely to suffer from treatment-emergent adverse events and that the drug is both safe and effective for obese patients.